Real time monitoring for tank level based on ISA100.11A using star topology - Osman, Zafrul Azman (2015)
The use of wireless for data transmission and control system is a method that better and easier, especially for the oil and gas industry. Wireless methods generally have few protocols so that the data sent is not affected. If the data submitted is incorrect, it will affect the system to be controlled. By using the ISA100.11a, wireless security protocol can send data and control safely. The focus of this project is focused on a different network topologies, namely STAR protocol to be used by ISA100.11a. These networks are used to gain a faster response time within a range of less than 100M. The response time is obtained for both the network topology can be used to control digital logic control system uses data to ensure that it really is implemented in line with the process